Understanding the balance between additives' miscibility and plasticisation effect in polymer composites: a computational study. Issue 13 (15th March 2023) - Giunta, Giuliana; Smith, Lois; Bartha, Kristof; Karimi-Varzaneh, H. Ali; Carbone, Paola
Abstract : Plasticisers are small organic molecules added to polymer composites to modify their processability by adsorbing on the filler's surface or dispersing into the polymer matrix. Here we show how just small topological changes to the molecule's structure affect miscibility. Abstract : Plasticisers are small organic molecules routinely added to polymer composites that modify the processability of the compounds by adsorbing on the filler's surface or dispersing into the polymer matrix. Here using a simple yet chemically specific coarse-grained model, we demonstrate that the filler surface coverage and the degree of dispersion into the polymer matrix can be tuned without modifying the chemistry of the plasticisers but only by varying their conformational flexibility. We show that when the adsorption mechanism and clustering into the bulk are entropically driven as in this work, this is a general phenomenon independent on the polymer chemistry and its molecular weight. Our findings suggest a simple practical design rule that requires only minor modifications of the plasticisers' chemistry to achieve maximum adsorption onto the filler surface or dispersion into the polymer matrix.